Houses Without Foundations: On Belonging in Palestinian Women’s Cinema - Colleen Jankovic (e-cadernos ces)
This article analyzes several Palestinian women’s films, in which damaged or compromised (occupied, besieged) houses nevertheless serve as the grounds for building a sense of home, claiming belonging, and fostering collectivity. Using the house as both a figural and a material frame for exploring how Palestinian women filmmakers posit questions of sociality and collectivity in constrained contexts of dispossession, dispersion, and siege, this article argues that films such as Annemarie Jacir’s 2008 Salt of This Sea and Alia Arasoughly’s 2006 short The Clothesline envision forms of belonging that defy conventional national modes. To account for these alternative forms of belonging and unbelonging, the article draws from queer diasporic, queer of color, and women of color feminist critiques, ultimately arguing that these films posit neither a clear politics of resistance nor a hopeful vision of future possibilities, but rather compel a persistent internal critique of community-building, nation/home, and solidarity.